Synthesis, Characterization and Catalytic Activity of Cu/Cu2O Nanoparticles Prepared in Aqueous Medium - Sayed M. Badawy; R. A. El-Khashab; A. A. Nayl (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Copper/Copper oxide (Cu/Cu2O) nanoparticles were synthesized by modified chemical reduction method in an aqueous medium using hydrazine as reducing agent and copper sulfate pentahydrate as precursor. The Cu/Cu2O nanoparticles were characterized by X-ray Diffraction (XRD), Energy Dispersive X-ray Fluorescence (EDXRF), Scanning Electron Microscope (SEM), and Transmission Electron Microscope (TEM). The analysis revealed the pattern of face-centered cubic (fcc) crystal structure of copper Cu metal and cubic cuprites structure for Cu2O. The SEM result showed monodispersed and agglomerated particles with two micron sizes of about 180 nm and 800 nm, respectively. The TEM result showed few single crystal particles of face-centered cubic structures with average particle size about 11-14 nm. The catalytic activity of Cu/Cu2O nanoparticles for the decomposition of hydrogen peroxide was investigated and compared with manganese oxide MnO2. The results showed that the second-order equation provides the best correlation for the catalytic decomposition of H2O2 on Cu/Cu2O. The catalytic activity of hydrogen peroxide by Cu/Cu2O is less than the catalytic activity of MnO2 due to the presence of copper metal Cu with cuprous oxide Cu2O. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)